Electrophoretic Mobility of Red Blood Cells in Patients with Severe Forms of Intoxication - I. Ya. Golovetsky; V. V. Moroz; L. S. Biryukova; G. I. Kozinets; O. V. Popova (Общая реаниматология)
Objective: to study the diagnostic and prognostic value of changes in red blood cell electrophoretic mobility (RBCEM) in patients with infectious and noninfectious forms of intoxication.Materials and methods. A cytoferometer (Opton) was used to determine RBCEM; venous blood samples taken on heparin were studied. Thirty patients with peritonitis (infectious intoxication) and 22 patients with a pancreatic tumor and mechanical jaundice (noninfectious intoxication) were examined. All the patients received standard therapy for this disease. Eight out of 30 patients died on days 3—10 postoperatively.Results. On postoperative days 1—2, the values of RBCEM were outside the lower normal range in 90% of the patients with peritonitis (p<0.01). At the same time the patients with a good outcome of the disease differed from those who subsequently died (p<0.05), but they did not differ in the severity of the disease (APACHE II scale) and the results of laboratory and clinical blood tests. On days 7—14 versus days 1—2 after surgery, the survivors, unlike the deceased, showed an increase in RBCEM (p<0.05) and a reduction in disease severity by the APACHE II scale (p<0.05). On admission, in 95% of patients with pancreatic tumor, the values of RBCEM were beyond the lower normal range (p<0.01). Seven-day disintoxicant therapy caused a rise in this index.Conclusion. Intoxication with infectious and noninfectious agents leads to lower RBCEM. In patients with general peritonitis, the values of this index and its changes are of diagnostic and prognostic value in evaluating the severity and outcome of the disease and the efficiency of performed therapeutic measures.